Diagnostic and prognostic significance of ALU-based cell-free DNA in colorectal cancer: a systematic review and meta-analysis - Taghizadeh-Teymorloei, Mohammad; Alizadeh, Leila; Matin, Somaieh; Jafari-Koshki, Tohid; Karimi, Abbas (Frontiers in Oncology, 2024)
Introduction Colorectal cancer (CRC) is a major global health concern. This study aimed to investigate the role of ALU-based cell-free DNA (cfDNA) in the diagnosis and prognosis of CRC. Methods We selected relevant literature from PubMed, Scopus, Web of Science, EMBASE, and Science Direct databases based on strict inclusion and exclusion criteria. 17 eligible studies were included in the final analysis (13 studies for diagnostic and 4 studies for prognostic meta-analysis). The search covered relevant publications up to July 1, 2024. Results The pooled sensitivity, specificity, and diagnostic odds ratios (DOR) of ALU-based cfDNA in CRC diagnosis were 0.81 (95% CI= [0.70, 0.89]), 0.90 (95% CI= [0.70, 0.96]), and 40.58 (95% CI= [17.87, 92.19]), respectively. The area under the ROC curve was 0.92 (95% CI= [0.89, 0.94]). Patients with higher concentrations of plasma/serum ALU-based cfDNA had poorer overall survival (OS) (pooled hazard ratio = 2.33 ([95% CI= [1.80, 3.03]). Conclusion The current evidence supports the utility of circulating ALU as a promising non-invasive diagnostic and prognostic tool for CRC. Furthermore, as a potential biomarker, ALU-based cfDNA could play a significant role in clinical application. Clinical implications The evidence suggests that circulating ALU-based cell-free DNA (cfDNA) holds promise as a non-invasive diagnostic and prognostic tool for colorectal cancer, potentially enhancing clinical decision-making. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier PROSPERO (CRD42023486369).